Validity and Reliability of the Turkish Version of the Acceptance of Cosmetic Surgery Scale (ACSS) - KARAKOÇ, AYŞE; KADIOĞLU, HASİBE; KARACA, SEMRA (KARE PUBL, 2017)
Objectives: Because cosmetic/aesthetic surgery has increased dramatically worldwide, it is necessary to evaluate the reasons and psychosocial situation of the persons proposing to undergo this surgery before any surgical intervention. The aims of the current study were to examine the validity and reliability of the Acceptance of Cosmetic Surgery Scale (ACSS) among Turkish persons. Methods: This methodological study was conducted with 584 participants. Content and construct validity studies were carried out to test the validity of the scale. The construct validity was analyzed with confirmatory factor analysis (CFA). For the scale's reliability, the techniques of internal consistency and consistency over time were used. Results: The Turkish adaptation of the ACSS was found to be valid, exhibiting a content validity index in the range of 0.80-1 on the item level, and 0.90 at the scale level. The scale displayed a three-factor structure. The total Cronbach's alpha coefficient for the scale was 0.92; the Cronbach's alpha coefficient for Factor 1 (Interpersonal) was 0.81; and 0.86 for Factor 2 (Social). The Cronbach alpha coefficient for Factor 3 (Consider) was 0.90. Conclusion: The ACSS is a valid and reliable tool that can be used in assessing acceptance of cosmetic surgery.
Keywords: Cosmetic/aesthetics surgery; reliability; scale translation; validity; BODY-IMAGE; ATTITUDES; ANXIETY